Evaluation of the Use of Antihypertension Medications in Inpatient Chronic Kidney Failure Patients at X Hospital, Jambi City, 2022 - Sepriani; Medi ANDRIANI; Aisa Dinda MITRA (RADINKA JOURNAL OF HEALTH SCIENCE, 2023)
Chronic kidney disease is a global public health problem with increasing prevalence and incidence of kidney failure, poor prognosis, and high costs. The incidence of CKD in Jambi Province was 30,554 cases. This study aims to determine the use of antihypertensive drugs in inpatient chronic kidney failure patients at Hospital X, Jambi City. This research is a descriptive study with retrospective data collection. The research sample was antihypertensive drugs used by patients with chronic kidney failure at Hospital X Jambi City for the period January to February 2022, totaling 50 prescriptions. The sampling technique is purposive sampling. The research instrument is a data collection sheet. The results of the study showed that 52.0% of the patients were female, 36.0% of the patients were in the late elderly category, the class of drugs most commonly used was Calcium Channel Blockers, namely 47.6%, the majority of respondents used a combination drug, 62.0 %. The rationality of the drugs used shows that there is a 100% correct dose, 100% correct route of administration, 100% correct duration of drug administration, and 94.0% no drug interactions. The Wilcoxon test results showed that there was an influence of the use of antihypertensive drugs on the blood pressure of CKD patients (p-value=0.000). It is hoped that doctors will choose drugs with a lower interaction profile to reduce the risk of dangerous interactions.